Elaboración y aplicación de un manual de Técnicas y Estrategias de aprendizaje cooperativo juntos aprendemos, para el desarrollo de la Inteligencia Lingüística en los estudiantes de Segundo Año paralelo A dela Escuela Fausto Molina de la ciudad de Riobamba en el período Académico 2013-2014 - Fernández Cepeda, Olga Cumandá (2015)
After conducted the preliminary study, it was determined that the primary objective of this research was to explore, analyze and determine the cooperative learning as a strategy for successful teaching in small groups, each one with students of varying skill levels using a variety of activities to enhance linguistic intelligence and determine the functionality of cooperative learning strategies as an alternative to the problem in this research, the reality is that in school is not used the cooperative learning as a technique in teaching and learning which leads to a low development of linguistic or verbal intelligence in children of the second year of Basic Education parallel "A" of School Fausto Molina in Riobamba city; for this reason it was decided to conduct this research to facilitate the work of teachers and provide appropriate tools to improve linguistic intelligence; through the development and implementation of a Manual of Techniques and strategies of cooperative learning. Constructivism is based on the subject develops his knowledge in relation to their environment, to achieve quality education and warmth, according to the policies of the Ten-Year Plan, National Plan for Good Living and the Principles of Critical Pedagogy also been taken reading from different perspectives, such as behavioral, Cognitivist and Partner constructivist, which define how the subject acquires and develops language learning, reading, and with it the understanding of it; understood as an interactive process between the text and the reader. One quasi-experimental research design was used, taking as example the entire selected population; relying on the descriptive and explanatory method; as a technique using observation sheets and questionnaires as essential tool; thirty-two (32) students. Using inductive, deductive and analytical methods - synthetic. Besides descriptive statistics, based on the results, then the corresponding analysis has reached the following conclusions and recommendations: It was shown that the application of the Manual Together learns the teamwork improve and allow the development of linguistic intelligence. Suggest to teachers that must use the Manual Together learns as a support tool it has practical exercises with the correct and consistent implementation, will help develop linguistic intelligence in students being studied. Using stories, proverbs, fables, riddles, jingles and funny texts according to the age of the students to encourage teamwork.